Understanding sociodemographic differences in climate behavior, climate policy acceptance, and political participation - Lena Lehrer; Lennart Hellmann; Cornelia Betsch (The Journal of Climate Change and Health)
Introduction: To mitigate the global health threat posed by climate change, multifaceted responses are required. In previous work, older, male, and highly educated individuals were shown to exhibit greater general readiness to act against climate change; the same is true for people living in larger communities. Yet, the sociodemographic effects may vary for the single facets of the readiness to act against climate change—namely individual climate-friendly behavior, acceptance of climate-protection policies, and political participation. Methods: Data from four waves (2022–2023) of the Planetary Health Action Survey (PACE) were analyzed (N = 3,830, nonprobabilistic representative German sample). Sociodemographic variables (gender, age, community size, education and others) and the three abovementioned facets of the readiness to act against climate change were assessed to examine their relationships. Results: Patterns varied between the indicators. Women and older individuals exhibited more climate-friendly behavior and policy acceptance. In contrast, levels of political participation were higher for men and younger individuals. Higher education was linked to less sustainable behavior, greater policy acceptance, and higher participation, while municipality size was only linked to the latter two. Additional analyses explore the relations between age and the constructs at item level. Conclusions: Findings underscore the importance of a nuanced understanding of people's readiness to act against climate change. Depending on communication objectives, different target groups may be relevant, e.g., do campaigners want to increase political participation vs. change individual behaviors. While older individuals exhibit greater readiness to act via individual behavior and policy acceptance, it is important to include young people in climate-communication efforts.